Trends in management of hip and knee osteoarthritis in general practice in Australia over an 11-year window: a nationwide cross-sectional survey - Kim L. Bennell, PhD; Clare Bayram, PhD; Christopher Harrison, PhD; Caroline Brand, MBBS; Rachelle Buchbinder, PhD; Romi Haas, PhD; Rana S. Hinman, PhD (Elsevier, 2021)
Background: We aimed to describe trends in knee and hip OA management by general medical practitioners (GPs) in Australia. Methods: We analysed cross-sectional survey data from the Bettering the Evaluation and Care of Health (BEACH) program (1,000 randomly-selected GPs annually recording 100 consecutive patient encounters) over two periods: Period one April 1, 2005-March 31, 2010 and period two April 1, 2010-March 31, 2016. This included data from 10,738 GPs and 1,073,800 patient encounters with 6,565 GPs and 9,196 patient encounters for hip/knee OA. Data were summarized using descriptive statistics and 95% confidence intervals around point estimates. Findings: Rate of knee OA problems managed by GPs increased in period two (7•1 (6•9-7•4) vs 6•2 (95% CI 6•0-6•5) per 1,000 all encounters), with a similar trend for hip OA. Encounter rates rose for some subgroups but remained stable for vulnerable subgroups. Although use of Medicare chronic disease management items, referral to allied health professionals and advice/education and lifestyle management (knee OA) increased, rates remained low. Use of MRI imaging rose. Overall medication rates were stable but substantially higher than non-pharmacological treatments. Declining reliance on non-steroidal anti-inflammatory drugs and glucosamine and increased reliance on paracetamol (knee OA) and opioids were demonstrated. Interpretation: GPs in Australia are more frequently managing knee and hip OA. While small changes in GP management actions occured, rates of recommended first-line non-pharmacological treatments remained low and imaging, medications, and surgical referral rates high. Strategies are needed to optimise lifestyle management and reduce low-value care, with attention to healthcare disparities. Funding: Funding was provided for this report by the National Health and Medical Research Council (NHMRC) Centre of Research Excellence in Translational Research in Musculoskeletal Pain (#1079078).